UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL DENGAN PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) PADA KELAS IV SD NEGERI 001 UKUI SATU - Asnimar ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the activity and motivation of students to learn social sciencesis still low. This is shown in their behavior when the following study social sciences. Based onthe test scores of the first half of social sciences with KKM (minimum completeness criteria)was 65 known that 58% of students have graduated KKM while 42% of students did notcomplete. Under the conditions described, we can conclude that student learning outcomesare still low. Researchers also conducted interviews with several students. Some students saidthat the conditions were not conducive classes, friends who like crowded in the classroom, theway teachers deliver material is less clear, the reason for the lazy student learning so thatlearning is low. The objectives to be achieved in this research is to determine the applicationof cooperative learning think pair share (TPS) in improving learning outcomes for socialsciences at the fourth grade students of SD Negeri 001 Ukui Satu. lessons classroom actionresearch (PTK) planned two cycle. Each cycle in action research consists of four stages,namely: 1) planning (planning), 2) the implementation of the (acting), 3) of observation(observing), 4) reflection (reflecting). This study was conducted in SD Negeri 001 Ukui Satuin the fourth grade, while the timing of this research is in the second semester of the academicyear 2016. In this classroom action research that is the subject of research is the students ofclass IV consisting of 34 students with a composition of 11 male students-Eighteen and 23female students. Data collection techniques in this study is the observation, testing,documentation and interviews.